Beverage Sensory Modification - Malfeito Ferreira, Manuel (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
This Special Issue on "Beverage Sensory Modification" presents a series of articles that feature the broad sense of sensory modification with regards to beverages, either by improving their flavor, taste, and mouthfeel properties, or through prevention of spoilage. The scope goes further than the usual technological measures that modulate sensory properties and includes psychological and cross-modal influences, where the sensory modification occurs in the subject's brain rather than as a result of modified physical-chemical properties of objects.